Characteristics, stability, and utilization of sulfuric natural water from Sebau East Lombok in reducing dissolved metals - Surya Hadi; Teguh Rifandi; Bakti Abdillah; Mozaik Al Qharomi; Lalu Riza Mahendra; L M Riza Rahman Hidayat; Dina Asnawati; Murniati Murniati (Journal of Degraded and Mining Lands Management, 2023)
This paper aims to characterize and test the stability of sulfuric natural water (SNW) from Sebau East Lombok as a sulfidation agent for several dissolved metals (Mn, Cu, Pb and Fe). The parameters used for SNW characterization are temperature, pH, DO, BOD, COD, TSS, and TDS. The sample was divided into two categories, namely the sample with preservation treatment and the sample without preservation, to study the stability of SNW. The SNW stability was determined by observing the SNW parameters in both samples at a storage time of 5, 10, 15 and 20 days and reacting them with dissolved metals. The SNW with preservation had reduced sulphide levels from day 1 to day 20, ranging from 59.24 mg/L to 17.70 mg/L, whereas the sample without preservation had decreased sulphide concentration from 52.46 mg/L to 9.56 mg/L. Furthermore, the SNW with preservation has a relatively superior metal reduction ratio than the sample without preservation. The maximum value of the deposition ratio for Mn metal was obtained on the fifth day with 57.60%, 83.45% for Cu, and 91.87% for Pb. This trend is not applicable for Fe, whereas the highest reduction (87.23%) was obtained on the the15th day's storage.